Right ventricular index for risk stratification of patients with pulmonary arterial hypertension - Sinning, Christoph Robert; Harbaum, Lars; Schrage, Benedikt; Rübsamen, Nicole; Magnussen, Christina; Waschki, Benjamin; Kleemann, Wilko H.; Baaske, Kaaja M.; Kögler, Maria; Ojeda, Francisco; Fischer, Christine; Benjamin, Nicola; et al. (Respiration, 2018)
Background: Right ventricular (RV) dysfunction is a major prognostic predictor in pulmonary arterial hypertension (PAH). Objectives: The objective of this study was to assess the prognostic impact of a newly developed index merging haemodynamic parameters into 1 variable. Methods: We retrospectively assessed 2 cohorts of 248 patients (164 from Hamburg and 84 from Heidelberg) with invasively diagnosed PAH. During a median follow-up time of 3.6 years (3.1 and 4.0 years for Hamburg and Heidelberg, respectively), the composite endpoint of all-cause mortality and lung transplantation occurred in 57 patients (53 and 4 patients for Hamburg and Heidelberg, respectively). The RV index was developed in the Hamburg cohort and validated in the Heidelberg cohort: (right atrial pressure × pulmonary vascular resistance)/mixed venous oxygen saturation. Results: Patients with a high RV index had a higher incidence of the combined endpoint in Kaplan-Meier analyses in the Hamburg and Heidelberg cohort (p = 0.017 and p = 0.034, respectively). The calculated RV index cut-off value was 91 and identified patients with a worse outcome in the Hamburg cohort and showed a trend in the Heidelberg cohort (p < 0.001 and p = 0.089, respectively). The RV index in Cox regression hazard models was an independent predictor of outcomes after adjustment for sex and age in both cohorts (Hamburg: hazard ratio [HR] 1.26 [95% CI 1.08, 1.47], p = 0.0027; Heidelberg: HR 2.27 [95% CI 1.46, 3.51], p < 0.001). A nomogram based on these results allowed risk stratification. Conclusion: Merging 3 haemodynamic variables into 1 variable, the RV index increased the prognostic power up to an independent risk factor. The RV index is easy to calculate and allows the construction of a nomogram for an individualized risk assessment.